2005
DOI: 10.1159/000083993
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and a 3-Year Follow-Up in Elderly Receiving Support at Home

Abstract: Background: Elderly receiving public services and care are often frail, suffer from chronic diseases, and sustain a high risk for malnutrition. Objective: To evaluate nutritional status and long-term outcome in elderly living at home. Methods: Of 507 eligible subjects receiving home care in five Swedish municipalities, we examined 353 (age 82 ± 7 years, 64% females). The subjects were interviewed, and the nutritional status was assessed by means of the Mini Nutritional Assessment (0–30 points; the lower the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
70
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 46 publications
11
70
0
5
Order By: Relevance
“…Older people living at home receiving regular home-care services are also more at risk than the free-living elderly of our study, as shown by Soini et al (2004), who found, also using the MNA instrument, that 3% of the subjects in their study were Nutritional status and osteoporosis H Salminen et al malnourished and 48% were at risk of malnutrition. Similar results were found in the study by Saletti et al (2005), who found that 8% of the elderly receiving public services and home care were malnourished and around 40% were at risk of malnutrition. The 3-year mortality was highly elevated for the malnourished and those at risk of malnutrition, 50 and 40%, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Older people living at home receiving regular home-care services are also more at risk than the free-living elderly of our study, as shown by Soini et al (2004), who found, also using the MNA instrument, that 3% of the subjects in their study were Nutritional status and osteoporosis H Salminen et al malnourished and 48% were at risk of malnutrition. Similar results were found in the study by Saletti et al (2005), who found that 8% of the elderly receiving public services and home care were malnourished and around 40% were at risk of malnutrition. The 3-year mortality was highly elevated for the malnourished and those at risk of malnutrition, 50 and 40%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The Mini-Nutritional Assessment (MNA), a test developed to determine the risk of malnutrition in older people (Guigoz et al, 1996), has been employed to detect nutritional deficiencies in institutional settings (Saletti et al, 2000) as well as in healthy general populations (Scheirlinckx et al, 1999). Moreover, this test has been found to predict mortality in geriatric patients (Persson et al, 2002) and in both an elderly Danish population and among free-living elderly Swedish subjects receiving public services and care (Beck et al, 2001;Saletti et al, 2005). In a comparison of ultrasound measurements of the calcaneus with MNA test scores in a population of institutionalized elderly women, Gerber et al (2003) observed no correlation at all between the MNA score and the ultrasound parameter Speed of Sound (SOS) and only a weak trend towards a correlation with the Broadband Ultrasound Attenuation (BUA).…”
Section: Introductionmentioning
confidence: 99%
“…6 A low MNA score, indicating malnutrition, has been associated with longer hospital stays, 7 lower quality of life 8 and an increased mortality rate. [9][10][11][12] The initial part of the MNA test constitute the MNA-short form (MNA-SF) and has been shown to have a good correlation with the full MNA test. 13 MNA's ability to predict mortality has nearly exclusively been studied in hospitals, nursing homes and patients with professional care at home.…”
Section: Introductionmentioning
confidence: 99%
“…13 MNA's ability to predict mortality has nearly exclusively been studied in hospitals, nursing homes and patients with professional care at home. [9][10][11][12][14][15][16][17][18] However, the great majority of the elderly are free-living. In fact, in 2009, 94% of Swedish persons aged X65 years were living at home, according to the Statistics Sweden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation